How do I solve this problem?

3 X n = 2

3 X n = 2

How do I solve this problem?

3 X n = 2

3 X n = 2

X2-12x-27=0

Solve using the zeros or intersect method 4x^2+12x-27=0

3 girls are traveling on a bus, each girl is holding 3 baskets in each hand, in each basket there are 3 cats each cat has 3 little kittens, one of the girls is getting off the bus how many legs are there in the bus?

Simplifying

3(2x + -4) = 3x + -1(5 + -1x)

Reorder the terms:

3(-4 + 2x) = 3x + -1(5 + -1x)

(-4 * 3 + 2x * 3) = 3x + -1(5 + -1x)

(-12 + 6x) = 3x + -1(5 + -1x)

-12 + 6x = 3x + (5 * -1 + -1x * -1)

-12 + 6x = 3x + (-5 + 1x)

Reorder the terms:

-12 + 6x = -5 + 3x + 1x

Combine like terms: 3x + 1x = 4x

-12 + 6x = -5 + 4x

Solving

-12 + 6x = -5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.

-12 + 6x + -4x = -5 + 4x + -4x

Combine like terms: 6x + -4x = 2x

-12 + 2x = -5 + 4x + -4x

Combine like terms: 4x + -4x = 0

-12 + 2x = -5 + 0

-12 + 2x = -5

Add '12' to each side of the equation.

-12 + 12 + 2x = -5 + 12

Combine like terms: -12 + 12 = 0

0 + 2x = -5 + 12

2x = -5 + 12

Combine like terms: -5 + 12 = 7

2x = 7

Divide each side by '2'.

X = 3.5

Simplifying

x = 3.5

3(2x + -4) = 3x + -1(5 + -1x)

Reorder the terms:

3(-4 + 2x) = 3x + -1(5 + -1x)

(-4 * 3 + 2x * 3) = 3x + -1(5 + -1x)

(-12 + 6x) = 3x + -1(5 + -1x)

-12 + 6x = 3x + (5 * -1 + -1x * -1)

-12 + 6x = 3x + (-5 + 1x)

Reorder the terms:

-12 + 6x = -5 + 3x + 1x

Combine like terms: 3x + 1x = 4x

-12 + 6x = -5 + 4x

Solving

-12 + 6x = -5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.

-12 + 6x + -4x = -5 + 4x + -4x

Combine like terms: 6x + -4x = 2x

-12 + 2x = -5 + 4x + -4x

Combine like terms: 4x + -4x = 0

-12 + 2x = -5 + 0

-12 + 2x = -5

Add '12' to each side of the equation.

-12 + 12 + 2x = -5 + 12

Combine like terms: -12 + 12 = 0

0 + 2x = -5 + 12

2x = -5 + 12

Combine like terms: -5 + 12 = 7

2x = 7

Divide each side by '2'.

X = 3.5

Simplifying

x = 3.5

The problem can be solved for the value of x as follows;

3(2x-4)=3x-(5-x)

6x-12=3x-5+x

6x-12=4x-5

6x-4x=12-5

2x=7

x=7/2

x=3.5 is the answer.

3(2x-4)=3x-(5-x)

6x-12=3x-5+x

6x-12=4x-5

6x-4x=12-5

2x=7

x=7/2

x=3.5 is the answer.

Problem solve Method

3(2x-4)=3x-(5-x)

6x-12=3x-5+x

6x-12=4x-5

6x-4x=12-5

2x=7

divide

x= 7/2

Ans

x= 3.5

3(2x-4)=3x-(5-x)

6x-12=3x-5+x

6x-12=4x-5

6x-4x=12-5

2x=7

divide

x= 7/2

Ans

x= 3.5

Didn't find the answer you were looking for?